«LAND OF CONFUSION»: QUANTUM PHYSICS IN IR THEORY? - T. A. Alekseeva; A. P. Mineyev; I. D. Loshkariov (Vestnik MGIMO-Universiteta)
The article deals with the "Quantum mind"hypothesis which has been elaborated in recent works of Alexander Wendt. It is ultimately significant to analyze this hypothesis and to expand on its difficulties and possible inconsistencies given Wendt's credentials in IR theorizing. It allows us to develop a new approach and promising research program on the basis of the hypothesis and its critical reflection. Wendt's quantum physicalism (or holism) implies serious philosophical injury and outstanding usage of different science disciplines' apparatus including physics, biology, and psychology. Thought-provoking approach of Wendt boosts researching efforts within the field of political philosophy, world politics and international relations. The main feature of the hypothesis is the idea of quantum nature in social and political processes which appears to be the consequence of epistemological authority of current science. Alexander Wendt proposes several explanations for quantum foundations within the political and social processes including wide-known "agent-structure" dilemma. According to him, invisibility of social structures does not lead to denial of its existence. Firstly, social structures emerge from the space of possibilities and are not directly dependant on material factors. Secondly, invisibility and its acceptance in different areas are parts of science clarification in many areas including quantum physics. The article discuses how quantum physics principles such as particle-wave dualism, superposition and size absoluteness can be useful in social and political studies. This allows us to demonstrate the given hypothesi' potential in research field of social sciences with regard to international relations and world politics.